Peran Guru Pendidikan Agama Islam dalam Melaksanakan Program Tahfidz Al-Qur'an di SMA Negeri 6 Kota Padang - Gusti, Ilham; Murniyetti, Murniyetti (Lembaga Yasin AlSys, 2023)
In the world of education, teachers have various important roles in shaping the personality of their students so that they become figures who are able to educate the life of the nation, have faith, are broad-minded, and are beneficial to many people. So it needs to be studied in depth regarding the role of Islamic Religious Education teachers who play an active role in forming, fostering, and guiding the student learning process, especially in memorizing the Al-Qur'an. This research aims to determine the role of PAI teachers in implementing the tahfidz program at SMAN 6 Padang. In this study the authors used a qualitative method with a descriptive method because the object of research relied on observation, interviews and documentation of informants, namely PAI teachers and students of SMAN 6 Padang. Furthermore, the data analysis techniques in this research are data reduction, data presentation and verification. The results of this study reveal several findings regarding the role of PAI teachers at SMAN 6 Padang, namely (i) Spiritual Advisors, (ii) Al-Qur'an Teachers, (iii) Trainers and Motivators, (iv) Supervisors and Assessors, (v) Liaison with parents, (vi) Moral Educators.